Microperimetry differences in macular sensitivity threshold between first and second tested eyes - Junqueira,Natacha B. (2021)
ABSTRACT Purpose: To comparatively assess the macular sensitivity threshold of microperimetry and the fixation stability between the first (right) and second (left) tested eye of normal participants. Methods: Thirty healthy patients were randomly assigned to two groups. The participants underwent microperimetry in the fast mode and expert mode in groups I and II, respectively. Each participant underwent a single test and the right eye was tested first. Results: The mean macular sensitivity threshold (± standard deviation [SD]) was 24.5 ± 2.3 dB and 25.7 ± 1.1 dB in the first (right) and second (left) eyes of group I, respectively (p=0.0415) and 26.7 ± 4.5 dB and 27.3 ± 4.0 dB in the first (right) and second (left) eyes of group II, respectively (p=0.58). There was no statistically significant difference between eyes in either group (p=0.1512). Regarding fixation stability (evaluated in the microperimetry expert mode group), the mean ± SD percentage of fixation points within the 1-degree central macula (P1) was 87.9 ± 11.5% in the right eye and 93.8 ± 6.6% in the left eye. The paired t-test did not show a statistically significant difference between eyes (p=0.140). Mean ± SD P2 value was 95.5 ± 4.9% in the right eye and 98.5 ± 2.1% in the left eye. The analysis demonstrated an increase in the percentage of fixation points in the second tested eye compared with the first one (paired t-test= 2.364; p=0.034). There was a negative correlation between the macular sensitivity threshold of the right eye and the duration of the examination for both groups (microperimetry expert mode: r=-0.717; p=0.0026; microperimetry in the fast mode: r=-0.843; p<0.0001). Conclusion: Mean macular sensitivity threshold was higher in the second tested eye in the microperimetry in the fast mode group and was similar in both eyes in the expert mode. Our data suggest that comprehension of the examination by the individual may impact the results of the microperimetry test.